Mewujudkan Nagari Maju Melalui Penerapan Good Governance dalam Pelayanan Publik Berbasis Kesehatan Ekonomi dan Hukum Islam (Universitas Negeri Padang, 2022)
Good governance is a value and benchmark in carrying out a good, orderly, and systematic system of government. In the current era, the central, regional, and rural command system which is part of the government system requires one-door public services, integrated with one another in order to realize and achieve government goals. Public services based on health, economics, and law are the objectives of the Indonesian government which are carried out and implemented by the current president. In order to achieve this goal, one of the ways to create an advanced Nagari is that represents public service in terms of the health system, economic system, and legal system that is implemented in the government, especially for remote areas (Nagari). Pesisir Selatan Regency, Nagari Lumpo is part of the government system in providing public services to the surrounding community. The impact of this public service is reflected in the welfare of the community and the achievement of the level of public education (graduate) that has been carried out by the regional government in realizing an advanced Nagari